2020
DOI: 10.1021/acs.inorgchem.9b03683
|View full text |Cite
|
Sign up to set email alerts
|

Pt(II) versus Pt(IV) in Carbene Glycoconjugate Antitumor Agents: Minimal Structural Variations and Great Performance Changes

Abstract: Octahedral Pt(IV) complexes ( 2Pt–R ) containing a glycoconjugate carbene ligand were prepared and fully characterized. These complexes are structural analogues to the trigonal bipyramidal Pt(II) species ( 1Pt–R ) recently described. Thus, an unprecedented direct comparison between the biological properties of Pt compounds with different oxidation states and almost indistinguishable structural features was performed. The stability profile of the novel Pt(IV) compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…It has been shown that the electronic spectra of metal complexes can be modulated by their interaction with proteins; for instance, a hyperchromic effect can be observed . Hence, potential changes of the UV–vis absorption properties of 1 – 3 upon interaction with lysozyme have been investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the electronic spectra of metal complexes can be modulated by their interaction with proteins; for instance, a hyperchromic effect can be observed . Hence, potential changes of the UV–vis absorption properties of 1 – 3 upon interaction with lysozyme have been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the electronic spectra of metal complexes can be modulated by their interaction with proteins; for instance, a hyperchromic effect can be observed. 42 Hence, potential changes of the UV−vis absorption properties of 1−3 upon interaction with lysozyme have been investigated. UV− vis spectra of 1−3 have therefore been recorded with and without the presence of lysozyme for 24 h. The corresponding comparative data (absorption values at λ = 433 nm) are depicted in Figure 4.…”
Section: Stability In Solutionmentioning
confidence: 99%
“…For uptake experiments, 1 × 10 6 cells of both immortalized and cancer cells were plated and treated with AP-1-encapsulated AFt at the concentration equal to IC50 (AP-1 concentration = 10.91 µM) for 48 h. At the end of incubation, cells were treated as described in Annunziata et al [52]. Each cellular pellet was transferred in a PE vial and digested in a thermo-reactor at 80 °C for 8 h with 2 mL of aqua regia (HCl supra-pure grade and HNO3 supra-pure grade in a 3:1 ratio).…”
Section: Cytotoxicity and Uptake Experimentsmentioning
confidence: 99%
“…Among these, sugars are an excellent example due to their biocompatibility, the possibility of modulating their chemico-physical properties, and the ability of selective recognition by cancer cells, known as the Warburg effect [19][20][21][22][23][24][25][26][27][28]. In this context, over the last few years, our research group has proposed new organometallic glycoconjugate platinum complexes as innovative anticancer agents [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%